Ferroic properties of nickel-ferrite based ceramic composites at room temperature - Guerra, J. D.S.; Portugal, R. J. [UNESP]; Silva, A. C. [UNESP]; Venet, M.; Betal, S.; Dutta, M.; Guo, R.; Bhalla, A. S. (My University, 2019)
Ceramic composites based on Pb(Zr,Ti)O3/NiFe2O4 (PZT–NFO) have been synthesized from the conventional solid-state reaction method. The ferroelectric and magnetic properties have been investigated at room temperature. The obtained results revealed excellent characteristics of both ferroic responses, which suggest the studied ceramic composite as a promising material for practical applications in magneto-electric related devices.
Keywords: ceramic composites; Multiferroics; PZT